Development of thermoplastic polyether ester elastomer microcellular foam with high resilience: Effect of chain extension on foaming behavior and mechanical properties. Issue 22 (3rd April 2023) - Yu, Leilei; Yu, Zhen; Yang, Lijuan; Wen, Shibao; Zhang, Zhen Xiu
Abstract: The lightweight development of thermoplastic polyether ester elastomer (TPEE) has been limited by its low‐melt strength. In this work, the epoxy chain extender ADR was employed to improve TPEE's melt strength in order to enhance its foamability by supercritical N2 (sc‐N2 ). The results showed that the melt strength of TPEE increased gradually with the increase of ADR content, which led to the uniformity of the foam cell structure and the improvement of its mechanical properties, that is, a high resilience of 82%. However, when ADR content exceeded 1.6 phr, the viscosity was too high to induce foaming. Remarkably, the maximum stress retention of TPEE foam with 1.6 phr ADR remained at 90% after 50 cycles of compression, while the strain recovery rate was higher than 85%. The prepared TPEE foam has excellent resilience and dynamic mechanical properties, which broadens its application in fields of midsole, sports equipment and transportation. Abstract :